The contributions of phonological awareness and naming speed to the reading fluency, accuracy, comprehension and spelling of Grade 3 IsiXhosa readers - Diemer, Maxine Nichole (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2016)
This thesis contributes to reading research in isiXhosa, where the role of various cognitive skills in reading has not yet been examined. One of the current debates in reading research centers on the contribution of cognitive skills, namely phonological awareness and naming speed, to reading. The exact relation between phonological awareness and naming speed, and their relation to literacy in different languages are also disputed. In this study, the contribution of phonological awareness and naming speed to literacy is examined in 52 Grade 3 isiXhosa speaking children. Measures for literacy included oral reading fluency, silent reading, comprehension and spelling. Phonological awareness was the biggest contributor to reading fluency, accuracy, comprehension and spelling, confirming that phonological processing is important for reading in all languages studied to date. The role of naming speed was narrower, contributing to the fluency and accuracy of reading only in the group with poor phonological awareness. The results can inform the teaching of reading isiXhosa where an approach that explicitly emphasises orthography-phonology relations at the phoneme level may be well suited especially since there are many letter groups to learn. This would enable higher accuracy in orthography-phonology correspondences and should also improve automaticity, which was lacking in the group with low levels of phonological awareness. The Psycholinguistic Grain Size Theory of reading can adequately inform the understanding of reading in isiXhosa, and findings from other languages with similar requirements can inform the teaching of reading in isiXhosa.
Keywords: Uncatalogued